واقع التقارير والقوائم المالية المرحلية في الشركات المساهمة العامة الفلسطينية المحدودة - حداد، جواد أحمد (جامعة القدس المفتوحة, 2012)
هدفت هذه الدراسة إلى التعرف إلى واقع التقارير والقوائم المالية المرحلية في الشركات المساهمة العامة المحدودة الفلسطينية، كما هدفت إلى التعرف إلى دور متغيرات الدراسة وهي: (المؤهل العلمي، وسنوات الخبرة) نحو موضوع الدراسة، ولتحقيق هدف الدراسة طُورت استبانة وتأكد الباحث من صدقها ومعامل ثباتها، وبعد عملية جمع الاستبانات رُمِّزت وأدخلت للحاسوب وعُولجت إحصائيًا باستخدام اللازمة الإحصائية للعلوم الاجتماعية (SPSS) وتوصلت الدراسة إلى أن هناك انتظامًا في إعداد التقارير المالية المرحلية، حيث تقوم الشركة بإصدار التقارير المرحلية في الموعد المحدد لها، حيث إن إصدار التقارير المرحلية في موعدها يساهم في زيادة ثقة المستثمرين في الشركة، كما تبين أن سوق فلسطين للأسواق المالية تُلزم الشركات بإصدار التقارير المرحلية في موعدها، وبناء على دلك توصي الدراسة ضرورة أن تلتزم الشركة بإعداد التقارير المرحلية حسب ما ينص عليه المعيار الدولي رقم (34) فيما يتعلق بإعداد التقارير، كما توصي بضرورة أن توضح التقارير المالية المرحلية تاريخ المركز المالي، وتاريخ بداية الفترة المالية ونهايتها. The purpose of this study was to investigate the reality of reports and periodical financial lists in Palestinian public shareholding limited companies. The study also aimed to identify the role of the variables of the study, namely, (qualification and years of experience) in the subject of study. To achieve the goals of the study, a questionnaire was developed. The validity and stability of the questionnaire were measured. The Statistical Package for Social Sciences (SPSS) was used to analyze the answered questionnaires. \ The study found that there is uniformity in the preparation of interim financial reports where the company is to issue progress reports on schedule, since the issuing of progress reports in a timely manner contributes to the increase in the confidence of investors in the company. It was also found that the Palestine Securities Exchange requires companies to issue progress reports in a timely manner. Therefore the study recommends the need for the company to be committed to the preparation of progress reports as required by the international standard number (34) regarding the preparation of reports. The study also recommends the need to clarify the interim financial reporting date of the financial position, and the date of the beginning and end of the financial period.
Keywords: الأسواق المالية -- فلسطين -- الشركات المساهمة -- الشركات العامة -- التقارير المالية -- محاسبة الشركات -- المعايير المحاسبية -- القوائم المالية -- القوانين و التشريعات